2011
DOI: 10.7763/ijeeee.2011.v1.54
|View full text |Cite
|
Sign up to set email alerts
|

SMEs Portfolio of e-Recruitment: Malaysian Perspective

Abstract: Abstract-The purpose of this study is the analysis of the possibilities and difficulties of e-recruitment practices for SMEs in Malaysia, elaborating their effectiveness, and explaining some practical and managerial implications concerning these actions. Statistical analyses and empirical findings expressed here show that the attitudes and opinions of SME executives towards e-recruitment are considered a sub-function of an integrated e-HRM and can be seen as a valued technological improvement in the main criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Poorangi et al [6] found that e-recruitment can help organizations to improve their employer brand, attract more qualified candidates, and reduce the time to hire.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Poorangi et al [6] found that e-recruitment can help organizations to improve their employer brand, attract more qualified candidates, and reduce the time to hire.…”
Section: Review Of Literaturementioning
confidence: 99%
“…E‐recruiting as a general process is job‐specific and offers computer‐assisted screening interviews and statistical prediction to aid in reducing recruiting costs, time‐to‐hire and employee turnover (Smith and Rupp, 2004). The findings of another study on this item showed that e-recruitment is basically an e-business system that enables enterprises to speed up the development of human capital (Poorangi and Khin, 2011).…”
Section: Theoretical Backgroundmentioning
confidence: 99%